Battery Ingestion in Children, an Ongoing Challenge: Recent Experience of a Tertiary Center - Lorenzo, Cristina; Azevedo, Sara; Lopes, João; Fernandes, Ana; Loreto, Helena; Mourato, Paula; Lopes, Ana Isabel (Frontiers in Pediatrics, 2022)
Introduction - Morbidity related to childhood battery ingestions (BI) has increased recently, due to the expanding use of larger lithium cells. A prompt endoscopic removal is vital to prevent severe complications in cases of esophageal batteries (EB). Material and methods - Retrospective, descriptive study of admissions for BI requiring endoscopic removal in a tertiary hospital’s paediatric emergency department (Jan 2011/Dec 2020). Results – We had 35 cases, with an increasing incidence in the last 6y; median age 26 m (8m-10y), witnessed ingestion in 86%. On the X-ray: 14 (40%) had an EB, 21 (60%) a gastric battery (GB). Symptoms were present in 57% (100% EB/24% GB) and vomiting was the most frequent (50%). Endoscopy revealed: EB 13 (37%), GB 17 (49%), duodenal battery 1 (3%), no battery 4 (11%). Median time to removal: EB 7h (2h-21d), GB 12h (2h-3d). All patients with EB on the X-ray (14), had severe mucosal injury (Zargar classification): grade IIIa 7 (50%), IIIb 5 (36%), IV 2 (14%). CT-scan showed perforation in 2 patients (total 4, 29% of EB). In patients with GB (21), 14 (67%) had mucosal damage, 13 (93%) mild (